Analysis of the Difference in the Importance of Instructors and Clinical Dental Hygienists for Oral Pathology Learning Objectives - Sun-Mi Lee; Jung-Hwa Lee; Eunae Sandra Cho (The Korean Society of Dental Hygiene Science, 2022)
Background: The purpose of this study was to identify the differences in the importance of oral pathology learning objectives for instructors and clinical dental hygienists and provide basic data that can guide learning objectives for acquiring practically necessary basic knowledge in the clinical field.Methods: Through the first-stage expert meeting, 27 items with less than four points out of 129 learning objectives in 15 detailed areas were deleted, 12 additional opinions were reflected, 114 learning objectives were set, and a survey was conducted with 253 people.Results: There were statistically significant differences in 92 items after examining the difference between professors and clinical dental hygienists. Among the areas of inflammation and repair, "Can explain the five symptoms of inflammation" had the highest with a score at 4.76 in the case of the professors. Among the areas of tooth damage, "Can explain abrasion" had the highest with a score at 4.61 in the case of the clinical dental hygienists.Conclusion: I would like to propose the existing 15 detail areas and 129 learning objectives as 14 detail areas and 98 learning objectives and strengthen the job competency of dental hygienists in the future. First, you need to develop competencies that are highly relevant to your work. Second, it is necessary to develop related textbooks and educational materials based on revised learning objectives and competencies. Third, based on revised learning objectives, the dental hygienist national examination should be improved. Through these changes in education, the education of oral and maxillofacial disease subjects should strengthen job competencies among dental hygienists with learning objectives that can be applied to actual clinical practice based on basic knowledge rather than knowledge orientation. In addition, it is possible to improve the quality of dental hygiene studies.